Getting to Phase 3: an Interview with Virginia S. Cowen, PhD, LMT - Kennedy, LMT, BCTMB, DrPH, Ann Blair (International Journal of Therapeutic Massage & Bodywork, 2017)
I feel that it is important to know the stories behind those who are working hard in the field to bring forward massage therapy research. Interviews with massage therapy researchers will now occasionally be included in the Journal as a new editorial feature. The first interview is with Virginia S. Cowen, PhD, LMT a New York State-licensed and NCB board-certified massage therapist with a PhD from Arizona State. She first became interested in massage therapy research while in massage therapy school, and her most recent work is investigating the integration of massage therapy into medical settings. Dr. Cowen states that massage therapy needs to move to Phase 3 research, and aligning with massage therapy practice and research on massage therapy education are areas ripe for research development. She urges the massage therapy profession to work together to develop clinical practice guidelines which could help move the profession forward.